Properties Of Biocompatible Mg-Zn Hydroxyapatite Composites Fabricated By Different Powder Mixing Techniques - Rodzi, Siti Nur Hazwani Mohamad (2015)
This work aims to investigate the mechanical performance and biodegradation behaviour of magnesium-zinc/hydroxyapatite (Mg-Zn/HA) composite that was fabricated via different powder mixing techniques. The powder mixing techniques of the composite was mainly divided into two, the first one is single step processing which involved the mechanical alloying and mechanical milling techniques, while the second is double step processing which involved the combination of mechanical alloying and mechanical milling. The optimum mechanical properties and biodegradation behaviour of the composite was achieved when the powders were prepared using mechanical alloying technique with the milling time of 4 hours and milling speed of 220 rpm. The composite prepared through the mechanical alloying technique was then subjected to various milling time to investigate the effect of milling time towards the properties of the composite. Mg-Zn/HA composite which was fabricated through the mechanical alloying technique and milled for 6 hours attained the best combination of improved corrosion behaviour as well as mechanical properties which is due to lowest corrosion rate (0.1487 mm/year by electrochemical polarization and 0.34 x 10-3 mm/year by immersion test) and acceptable microhardness (64 HV) and compressive strength (193 MPa). Fabrication of the biodegradable composite through the mechanical alloying technique within the 6 hours milling time was found to be suitable for the implant application, due to good mechanical strength and biodegradation behaviour. In term of biocompatibility, generally Mg-Zn/HAcomposite possessed good bioactivity characteristics through the immersion test, however immersion time of 24 hours was found to be insufficient to produce composites that can satisfy the initial bone mineralization which the Ca:P ratio in the range of 1:1 to 1:1.67. However, Mg-Zn/HA composite that was fabricated through single step processing of mechanical milling (Ca:P ratio of 1.76) was found to have the highest bioactivity over the other two composites that was fabricated through single step processing of mechanical alloying and double step processing.